PENENTUAN DAYA TAMPUNG BEBAN CEMARAN SENYAWA NITRIT DAN NITRAT MENGGUNAKAN PROGRAM QUAL2E DENGAN SIMULASI FISIK SUNGAI (STUDI KASUS : SUNGAI TUNTANG, JAWA TENGAH) - Mohamad Romadlon (Departemen Teknik Lingkungan Fakultas Teknik Universitas Diponegoro, 2013)
Nitrite (NO2-N) contaminant load capacity of Tuntang River at maximum stream is fulfill the quality standard Class I, II, or III by a capacity between 0 – 70,3 kg/day. Whereas Nitrate (NO3-N) contaminant load capacityof Tuntang River is fulfill the quality standard Class I and II by a capacity between 11414,15 – 11664,35 kg/day and fulfill the quality standard Class III and IV by a capacity between 23328,71 – 23578,91 kg/day. From Qual2E simulation by the rivers morphology (Mannings coefficient, side slope, width and slope) found when Manning coefficient is increase so contaminant load capacity of NO2 and NO3 is increase. But rivers side slope coefficient have not a influence significantly to contaminant load capacity of NO2 and NO3. If rivers width coefficient is increase so contaminant load capacity of NO2 is increase but it isn’t happen to contaminant load capacity of NO3 is constant. If rivers slope coefficient is increase so contaminant load capacity of NO2 is decrease but it isn’t happen to contaminant load capacity of NO3 is constant.